G42(P) Please reconcile, don't wait a while!. (May 2019) - Trivedi, A; Sharma, S; Ajitsaria, R; Davey, N
Abstract : Aims: In 2016 NICE published standards hat inpatients in an acute setting should have a reconciled list of their medicines within 24 hours of admission. Baseline data collected from our paediatric ward shows that medicines reconciliation by doctors is only completed 50% of the time. Evidence shows that medicines-related patient safety incidents are more likely when medicines reconciliation happens more than 24 hours after a person is admitted to an acute setting. The aim of this quality improvement project was therefore to ensure that 100<% of paediatric patients have their regular medications prescribed by midday the day after admission. Methods: The paediatric pharmacy team reviewed all paediatric inpatient drug charts from Monday to Friday for 12 weeks. The number of regular medications and the number of medicines reconciled was recorded each day. The effectiveness of various interventions were reviewed using PDSA cycles. Results: On average, 40 patients were reviewed each week. The mean reconciliation rate was 79% and the worst rate was 0%. 100% reconciliation was achieved on 34 occasions and was achieved continuously for the last three weeks of data collection. Conclusion: Multiple interventions occurred during this quality improvement project: teaching sessions for doctors, posters to raise awareness and questionnaires for parents/children to complete about their regular medications. The main factor for success in this project has been involving all members of the paediatric department including children and their parents. Additionally both A and E and the paediatric ward have both been involved ensuring consistency across the whole paediatric team.